Efficacy and drug persistence of baricitinib monotherapy is similar to combination therapy in patients with active RA: a prospective observational study - Bayat, Sara; Tascilar, Koray; Bohr, Daniela; Krönke, Gerhard; Simon, David; Knitza, Johannes; Hartmann, Fabian; Schett, Georg; Kleyer, Arnd (RMD Open, 2022)
BACKGROUND: Baricitinib (BARI) is approved for the treatment of rheumatoid arthritis (RA) after failure of conventional synthetic and biologic disease modifying anti-rheumatic drugs (cs/bDMARDs) in combination with methotrexate (MTX) or as monotherapy. However, real-world data are scarce regarding efficacy and drug persistence for BARI monotherapy (BARI-mono) versus its combination with MTX (BARI-combo). OBJECTIVE: To evaluate efficacy and drug persistence of BARImono compared with BARI-combo in routine clinical practice METHODS: Patients with RA who were switched to BARI were included in a prospective, monocentric cohort. Demographics, clinical outcomes, adverse events and medication were prospectively recorded every 3 months. Clinical efficacy was measured by DAS-28 ESR while drug persistence was measured as the time on drug. We estimated least-square mean DAS-28 scores over time using linear mixed effects models including time-group interactions. Kaplan-Meier method was used to estimate BARI survival and probability of remission over time. RESULTS: 139 patients (98 women; aged 58.4 (12.8) years; mean disease duration of 9.7 years) were included between 2017 and 2021. 46 patients received BARI-combo, 93 patients received BARI-mono. Mean DAS-28 ESR were not significantly but only numerically different between both groups at baseline and multiple timepoints over follow-up. DAS-28 ESR remission was attained at least once upto 48 weeks in 62% and 51% patients in BARI-combo versus BARI-mono group (log-rank p=0.64). Drug persistence was high (69 vs 67% at 48 weeks and 62% vs 56% at 96 weeks) and similar in BARI-combo-treated and BARI-mono-treated patients. b/ts DMARD naïve patients had lower mean DAS-28 scores over the follow-up and attained DAS-28 ESR remission earlier than patients with inadequate response to b/ts DMARDs (p=0.11). BARI was discontinued in 11/139 patients (7.9%) due to adverse effects. CONCLUSION: In routine practice, BARI is effective as monotherapy in case of MTX intolerance with overall high drug persistence rates. No new safety signals were observed.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Baricitinib; Combination treatment; Drug survival; Remission; Rheumatoid Arthritis